Hydrologic Export Is a Major Component of Coastal Wetland Carbon Budgets. Issue 8 (20th August 2020) - Bogard, Matthew J.; Bergamaschi, Brian A.; Butman, David E.; Anderson, Frank; Knox, Sara H.; Windham‐Myers, Lisamarie
Abstract: Coastal wetlands are among the most productive habitats on Earth and sequester globally significant amounts of atmospheric carbon (C). Extreme rates of soil C accumulation are widely assumed to reflect efficient C storage. Yet the fraction of wetland C lost via hydrologic export has not been directly quantified, since comprehensive budgets including direct estimates of lateral C loss are lacking. We present a complete net ecosystem C budget (NECB), demonstrating that lateral losses of C are a major component of the NECB for the largest stable brackish tidal marsh on the U.S. Pacific coast. Mean annual net ecosystem exchange of CO2 with the atmosphere (NEE = −185 g C m 2 year −1, negative NEE denoting ecosystem uptake) was compared to long‐term soil C burial (87–110 g C m 2 year −1 ), suggesting only 47–59% of fixed atmospheric C accumulates in soils. Consistently, direct monitoring in 2017–2018 showed NEE of −255 g C m −2  year −1, and hydrologic export of 105 g C m −2  year −1 (59% of NEE remaining on site). Despite their high C sequestration capacity, lateral losses from coastal wetlands are typically a larger fraction of the NECB when compared to other terrestrial ecosystems. Loss of inorganic C (the least measured NECB term) was 91% of hydrologic export and may be the most important term limiting C sequestration. The high productivity of coastal wetlands thus serves a dual function of C burial and estuarine export, and the multiple fates of fixed C must be considered when evaluating wetland capacity for C sequestration. Key Points: We present a complete carbon budget for the largest brackish tidal marsh in the Pacific United States Direct and indirect measurement showed 47% to 59% of fixed carbon is stored on site and most loss is through inorganic carbon export A compilation of global data sets showed lateral loss larger term in coastal wetland carbon budgets, relative to other terrestrial systems